Impact of robust treatment planning on single- and multi-field optimized plans for proton beam therapy of unilateral head and neck target volumes - Cubillos Mesías, Macarena; Troost, Esther Gera Cornelia; Lohaus, Fabian; Löck, Steffen; Richter, Christian; Stützer, Kristin (Radiation oncology, 2017)
Proton beam therapy is promising for the treatment of head and neck cancer (HNC), but it is sensitive to uncertainties in patient positioning and particle range. Studies have shown that the planning target volume (PTV) concept may not be sufficient to ensure robustness of the target coverage. A few planning studies have considered irradiation of unilateral HNC targets with protons, but they have only taken into account the dose on the nominal plan, without considering anatomy changes occurring during the treatment course.
Gesehen am 11.04.2018